Analisis Laporan Akuntabilitas Kinerja Instansi Pemerintahan Dinas Kebudayaan, Pariwisata, Pemuda dan Olahraga Kabupaten Kubu Raya - Beby Nurtesha Putri (Jurnal Akuntansi, 2019)
The purpose of this study was to find out about performance measurement in the Department of Culture, Tourism, Youth and Sports of Kubu Raya Regency. Performance measurement is carried out by the Government Agency Performance Accountability Report in accordance with Presidential Instruction No. 7 of 1999. Performance measurement is used as a basis for assessing failure program efficacy and execution and activities according to targets and objectives set in realizing the vision and mission of the Regency Government. The research method used in this research is descriptive method. Data obtained, then interpreted and analyzed, so that it can provide information that can be used to solve the problem at hand. The type of data used is secondary and primary data. The results of the study show performance for all existing targets and in accordance with the expected conditions. Suggestions the government needs to establish a standard reference in preparing reports. Keywords: Accountability, Agency Performance Accountability Report